2011
DOI: 10.1111/j.1365-2095.2009.00721.x
|View full text |Cite
|
Sign up to set email alerts
|

High n-3 HUFA levels in the diet of Atlantic salmon affect muscle and mitochondrial membrane lipids and their susceptibility to oxidative stress

Abstract: Atlantic salmon were fed one of four diets with increasing levels (11–58%of total fatty acids (FAs)) of n‐3 highly unsaturated FAs (HUFAs) in order to investigate the effect on muscle and mitochondrial membrane lipids and their susceptibility to oxidative stress. The high n‐3 eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) groups contained lower percentages of sphingomyelin and cardiolipin in total muscle than the intermediate n‐3 HUFA group. Cardiolipin and sphingomyelin are particularly susceptibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 58 publications
4
33
0
Order By: Relevance
“…These data agree with those showing marked modifications of FA of total mitochondrial PL by diet in rats (Lemieux et al 2008;Abbott et al 2010) and fish (Ushio et al 1997;Robin et al 2003;Guderley et al 2008;Østbye et al 2011;Martin et al 2013), and indicates the existence of mechanisms regulating FA within mitochondrial PL classes. Moreover, these data point to the importance of FA composition of specific PL classes in mitochondrial membranes.…”
Section: Diet Fatty Acid Composition and Mitochondrial Lipidssupporting
confidence: 92%
See 2 more Smart Citations
“…These data agree with those showing marked modifications of FA of total mitochondrial PL by diet in rats (Lemieux et al 2008;Abbott et al 2010) and fish (Ushio et al 1997;Robin et al 2003;Guderley et al 2008;Østbye et al 2011;Martin et al 2013), and indicates the existence of mechanisms regulating FA within mitochondrial PL classes. Moreover, these data point to the importance of FA composition of specific PL classes in mitochondrial membranes.…”
Section: Diet Fatty Acid Composition and Mitochondrial Lipidssupporting
confidence: 92%
“…Another explanation may be an increase in the degree of oxidative stress and, particularly, lipid peroxidation that would decrease membrane levels of PUFAs ). The observed decrease in mitochondrial total PL content in RO and especially, DHA groups could indicate the existence of high oxidative stress as was found in liver and muscle mitochondria of Atlantic salmon fed diets with a high level of n-3 LC-PUFA (Kjaer et al 2008;Østbye et al 2011). These studies also showed a decrease in CL content in mitochondrial membranes that agrees with data in the present study.…”
Section: Diet Fatty Acid Composition and Mitochondrial Lipidsmentioning
confidence: 91%
See 1 more Smart Citation
“…This theory would explain the huge differences in life The present data showed that mitochondria from 8-month-old zebrafish fed the DHA diet had higher levels of n-3 LC-PUFA and higher peroxidation index (PIn) value in the three main phospholipid classes, phosphatidylcholine (PC), phosphatidylethanolamine (PE) and cardiolipin (CL) (changes in PIn only significant for PE). These data are consistent with those showing considerable dietary modifications of FA composition of mitochondrial PL in rats (Lemieux et al 2008;Abbott et al 2010) and fish (Ushio et al 1997;Robin et al 2003;Guderley et al 2008;Ostbye et al 2011;Martin et al 2013;Almaida-Pagán et al 2015). However, they also indicate the existence of regulatory mechanisms of specific fatty acids within mitochondrial membranes as the observed changes did not clearly reflect the dietary compositions.…”
Section: Discussionsupporting
confidence: 89%
“…Lipid peroxidation in total lipid from mitochondria was double in fish fed the DHA diet than in fish fed the RO diet in 8-month-old fish. This indicated higher oxidative damage to mitochondrial lipids in young zebrafish fed the DHA diet, very likely due to the higher incorporation of long-chain polyunsaturated fatty acids (LC-PUFA), particularly DHA, in PL of mitochondrial membranes in fish fed diet DHA compared to fish fed the RO diet, as shown previously in liver and muscle mitochondria of Atlantic salmon, Salmo salar (Kjaer et al 2008;Ostbye et al 2011) and in liver mitochondria of rainbow trout (Oncorhynchus mykiss; Almaida-Pagán et al 2015). Several studies indicated that increase in dietary PUFA elevated the metabolic rate which would be very likely mediated by changes in membrane composition .…”
Section: Discussionmentioning
confidence: 61%